Pengaruh Sharia Governance Structure terhadap Pengungkapan CSR Berdasarkan Islamic Social Reporting Index - Rimi Gusliana Mais; Nuning Lufiani (Jurnal Manajemen, 2018)
The purpose of this study is to determine the effect of Shari'a Governance Structures with the disclosure level of Corporete Social Responsibility in Islamic banking in Indonesia. The related factors of Shari'a Governance Structures tested in this research are the supervising mechanism and ownership structure. The supervising mechanism is represented by the existence of the Sharia Supervisory Board measured using the Islamic Governance Score (IG-Score). While the ownership structure is measured using the ratio of temporary syirkah funds (Invesment Account Holders) and company size. In addition, this research also analyzes the disclosure level of CSR of Islamic Banking in Indonesia based on the ISR index. The sample was determined by purposive sampling method that Islamic Banking in Indonesia for year 2011 – 2015, with a total sample of 11 Islamic banking for a total observation in this study a total of 55 observations. The data used in this research is secondary data, in the form of financial report and annual reports that downloaded via the official website BI: www.bi.go.id. and site of each banks. Data were analyzed using pooled data regression that processed using Eviews version 7.0 software. ISR value obtained by analyzing each company’s annual report is based on content analysis. The results show that the Invesment Account Holders (IAH) has a positive and significant effect on CSR disclosure. However, the existence of the Shari’a Supervisory Board (SSB) and company size has no significant effect on the level of CSR disclosure in Islamic Banking in Indonesia.